A study of a comparison of financial performance in the banking sector, some evidence between Malaysia conventional bank and Islamic banks / Kamaliah Md Fadil - Md Fadil, Kamaliah (2009)
In order to fuffl the requirement for the project (FIN SS6) I have decided to construct a research untitled ‘A Comparison of Financial Performance in The Banking Sector, Some Evidence Between Malaysia Conventional Bank And Islamic Banks’ I hope that the research can give clearer picture about the financial performance among banks in Malaysia. The bank that involves in my research is the Bank totem and Bank Muamalat for the Islamic bank and CIMB and Hong Leong Bank for the conventional bank. Chapter one in this study is the overview, the problem statement, objectives significant, scopes, limitation, and the key terms of the study as well as the crating this reseacr project. Chapter two represent the literature review bassed on the financial performance, and the element that effect the financial performance such as the ratio for profitability, efficiency, liquidity, and leverage. Chapter three in this study represent the methodologies. The theoretical framework, data collection through the secondary data. Chapter four is about the finding and analysis that I have find out about the performance in the financial performance of the bank. The data is calculated one by one by bank and being compare to others bank to see which bank having good performance in research by taking average of all ratio. Chapter five represents the conclusion and recommendation of the study. In conclusion, researcher have stated that the reason on why the bank having losses or profit in their recent years last but not feast, the recommendation on all that significant to the study, in this reason also answer all problems statement that I have mention before.